Case–control study of paternal occupational exposures and childhood lymphoma in Great Britain, 1962–2010 - Bunch, K; Kendall, G; Stiller, C; Vincent, T; Murphy, M (Springer Nature, 2019)
Background This nationwide study investigates associations between paternal occupational exposure and childhood lymphoma. Methods The UK National Registry of Childhood Tumours provided cases of childhood lymphoma born and diagnosed in Great Britain 1962–2010. Control births, unaffected by childhood cancer, were matched on sex, birth period and birth registration sub-district. Fathers’ occupations were assigned to one or more of 33 exposure groups and also coded for occupational social class. Results We analysed 5033 childhood lymphoma cases and 4990 controls. Total lymphoma and the subgroups Hodgkin, Burkitt and non-Hodgkin lymphoma were considered separately. No one exposure was significantly associated with increased risk within all subgroups and for total lymphoma. However, exposure to “ceramics and glass” was significantly associated with increased risk of total lymphoma, Hodgkin and non-Hodgkin lymphoma. Paternal lead exposure was associated with Burkitt lymphoma and exposure to metal fumes was associated with Hodgkin lymphoma. Conclusions This study provides no support for previous suggestions of an association between childhood lymphoma and paternal occupational exposure to pesticides, solvents/hydrocarbons or infections potentially transmitted by father’s social contacts. An association with exposure to “ceramics and glass” was noted for the two major lymphoma subtypes together comprising 80% of total lymphoma.